Person-Oriented Organization of Academic Process - the Way of Genuine Flexibility and Individualization of Educational Curricula - B. A. Sazonov (Russian State Vocational Pedagogical University, 2015)
The paper deals with the necessity for Russian universities to switch over from the conservative stream-group scheduling to progressive individual scheduling of educational process where each particular student becomes an object of planning and implementing the higher educational curricula. The new liberal student- centered form called the «credit system» or in Russian variant the «credit units system» brings forward the students interests and rights. Gradually, such system tends to prevail in the world environment of vocational education, though in Russian higher school it still exist as an experiment and is not fast adopted. The prevailing stream-group model of educational process with steady group division throughout the whole academic period indicates our serious technological lagging behind the leaders of the world educational market. Rejection of traditional stream-group educational model and steady group formation brings about new opportunities for Russian universities providing real flexibility and individualization of educational curricula, giving students the option for individual term planning and scheduling, as well as the right for choosing teachers. Combining the modern approach to students' assessment and person-oriented organization of academic process, the complete mass adoption of the model in question in bachelor and specialists training can guarantee a qualitative leap in developing Russian higher educational system.